IMPROVING READING COMPREHENSION OF THE FOURTH-SEMESTER ENGLISH STUDENTS OF MAYJEN SUNGKONO UNIVERSITY USING RECIPROCAL TEACHING - Lus Firdaus Zakiya (Pimpinan Cabang Muhammadiyah Kramat Jati, 2021)
The method adopted in this study was classroom action research. The procedure and implementation process performed one cycle of four actions. After four actions have been performed, mutual education can improve students' reading comprehension in three stages. They are: (1) Look-ahead activities focus on activating students' prior knowledge. (2) Reading activities focus on the implementation of mutual education. (3) Post-reading activities focus on reaffirming students' understanding of the text. The final activity is managing quizzes. Students take individual tests without the help of other students or teachers. As a result of the test, the average student score was 73.75 and the lowest student score was 50. Finally, we could conclude that mutual instruction was able to improve students' reading comprehension. In addition, the students are more motivated and active to learn with the method. They learn to work together in a group with different abilities and to help each other.